DEVELOPMENT OF INTEGRATED ISLAMIC-BASED STUDENT WORKSHEET IN LINEAR PROGRAM MATERIAL TO FACILITATE MATHEMATICAL MODELING SKILLS - Khumairoh, Aisyah; Masamah, Ulfa; Adiafidah, Rosa Amalia (Program Studi Magister Pendidikan Matematika, Universitas Siliwangi, 2026)
This study aims to develop an integrated Islamic Student Worksheet on linear programming material to facilitate students' mathematical modeling abilities. This study uses the Research and Development (RD) method with the ADDIE development model, which consists of five stages: Analysis, Design, Development, Implementation, and Evaluation. In the analysis stage, a needs study and curriculum analysis were conducted, followed by the design of student worksheet that combines linear program material with islamic values. The validation results show that student worksheet obtained a percentage of 82.8%, which is included in the valid category, making it suitable for use as teaching material. The implementation of student worksheet has been carried out in the classroom, and the evaluation stage has been completed successfully. The practicality test results also showed that the student worksheet obtained an average score of 83.5% with practical criteria. The N-Gain test results showed an increase in mathematical modeling skills of 0.43 and Islamic financial literacy of 0.59 in the moderate category. This study produced an student worksheet integrated with Islamic values that supports contextual and meaningful mathematics learning.